1994
DOI: 10.1152/ajpheart.1994.266.4.h1541
|View full text |Cite
|
Sign up to set email alerts
|

Microvascular compression during myocardial ischemia: mechanistic basis for no-reflow phenomenon

Abstract: Alterations in fiber size and capillary diameter were highly correlated with perfusion deficits after myocardial ischemia. After 5 (n = 3) and 30 (n = 5) min of global normothermic ischemia, isolated rabbit hearts were perfused with India ink and then with glutaraldehyde. Morphometric techniques were used to determine mean fiber cross-sectional area [a(f)], mean effective capillary diameter [d(c)], total and perfused capillary number per fiber area, and capillary length per fiber volume in subepicardium (Epi) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
49
0
4

Year Published

1997
1997
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(53 citation statements)
references
References 0 publications
0
49
0
4
Order By: Relevance
“…In relation to post-ischaemic reflow, it has been suggested that microvascular compression is the major determinant of postischaemic coronary flow (Nevalainen et al 1986;Manciet et al 1994). The unloaded and isovolumically contracting hearts presented an interesting opportunity to test this notion.…”
Section: Responses To Ischaemia-reperfusion: Isovolumic Contraction Vmentioning
confidence: 99%
“…In relation to post-ischaemic reflow, it has been suggested that microvascular compression is the major determinant of postischaemic coronary flow (Nevalainen et al 1986;Manciet et al 1994). The unloaded and isovolumically contracting hearts presented an interesting opportunity to test this notion.…”
Section: Responses To Ischaemia-reperfusion: Isovolumic Contraction Vmentioning
confidence: 99%
“…During reperfusion, accumulation of leukocytes in the microvasculature that leads to mechanical plugging (1,7,8) and interactions with platelets, the endothelium, and cardiomyocytes has been put forward to explain the progression of anatomic no reflow. In addition, tissue edema (27) and oxygen free radicals (6) derived from polymorphonuclear cells, the xanthine oxidase reaction, or mitochondria may be involved in reperfusion-related expansion of anatomic no reflow (34) and hence contribute to the size of perfusion defects after 3 h of reperfusion. Accordingly, the irreversible damage of cardiomyocytes could initiate a chain reaction and serve as the inflammatory stimulus that leads to leukocyte accumulation, oxygen free radical production, tissue edema, and, subsequently, microvascular perfusion defects with the observed close accordance in size and spatial distribution of no reflow and necrosis.…”
Section: Microvascular and Myocardial Damage In Reperfused Infarctsmentioning
confidence: 99%
“…Several mechanisms can initiate no-reflow in previously ischemic myocardium: (a) embolization of particulate atherosclerotic debris from the culprit lesion into the coronary microcirculation, both after mechanical or thrombolytic reopening of epicardial coronary arteries [9]; (b) platelet and platelet/leukocyte aggregates which are either released from the culprit lesion or form in the microcirculation [2]; (c) intense vasoconstriction in response to soluble factors (endothelin, serotonin, thromboxane) which are released from the culprit lesion [12]; (d) extravascular compression of the capillary bed by edema of the surrounding myocardium and interstitium [15]; and (e) edema and physical disintegration of the capillary vascular structures per se [13]. These pathomechanisms are not mutually exclusive, and their contribution to the no-reflow phenomenon may vary temporally and spatially as well as between different experimental models and individual patients.…”
mentioning
confidence: 99%